2010
DOI: 10.1007/s12026-010-8165-y
|View full text |Cite
|
Sign up to set email alerts
|

Biology and pathophysiology of the new human retrovirus XMRV and its association with human disease

Abstract: Xenotropic murine leukemia virus-related virus (XMRV) is a new human retrovirus originally identified in prostate cancer patients with a deficiency in the antiviral enzyme RNase L. XMRV has been detected with varying frequencies in cases of prostate cancer and chronic fatigue syndrome (CFS), as well as in a small proportion of healthy individuals. An etiologic link between XMRV infection and human disease, however, has yet to be established. Here, we summarize existing knowledge regarding the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…The R462Q mutation decreased RNase-L activity by three-fold in transfected cells thereby correlating reduced RNase-L activity with increased prostate cancer risk as predicted for a tumor suppressor (123). Subsequent studies both confirmed and refuted a relationship between RNASEL mutations and prostate or other cancers suggesting that additional factors or study parameters contribute to the impact of RNASEL on tumorigenesis (124, 125). For example, a recent study found an association of R462Q homozygosity with prostate cancer risk only in cases prior to the use of PSA as a biomarker when detection may have occurred at a more advanced stage of the disease (126).…”
Section: Biologic Roles For Rnase-l and Disease-associated Alteratmentioning
confidence: 92%
See 1 more Smart Citation
“…The R462Q mutation decreased RNase-L activity by three-fold in transfected cells thereby correlating reduced RNase-L activity with increased prostate cancer risk as predicted for a tumor suppressor (123). Subsequent studies both confirmed and refuted a relationship between RNASEL mutations and prostate or other cancers suggesting that additional factors or study parameters contribute to the impact of RNASEL on tumorigenesis (124, 125). For example, a recent study found an association of R462Q homozygosity with prostate cancer risk only in cases prior to the use of PSA as a biomarker when detection may have occurred at a more advanced stage of the disease (126).…”
Section: Biologic Roles For Rnase-l and Disease-associated Alteratmentioning
confidence: 92%
“…Thus a model in which XMRV promotes oncogenic transformation and is countered by the anti-XMRV activity of RNase-L to mediate prostate cancer tumor suppressor activity has been supported by some studies. However, conflicting reports preclude a consensus on the role of XMRV in the etiology of prostate cancer and its association with RNase-L (124, 125, 131). These studies highlight the need for further investigations into the relationships between these parameters as risk factors and as potential therapeutic targets.…”
Section: Biologic Roles For Rnase-l and Disease-associated Alteratmentioning
confidence: 99%
“…The prominence of GRE in the gamma-and lentiviral genomes suggests that their life cycles are dependent on the host's GR regulatory system (Rusmevichientong & Chow, 2010). Glucocorticoids stimulate gamma-retroviral promoter activity in multiple cell types.…”
Section: Effects Of Activated Glucocorticoid Receptors On Gamma-retromentioning
confidence: 99%
“…Other potential applications of MS-based proteomic techniques are the identification of tumorrelated viruses such as Kaposi's sarcoma-associated herpesvirus or the identification of other novel viruses such as xenotropic murine leukemia virusrelated virus, a new human retrovirus originally identified in prostate cancer patients with a deficiency in the antiviral enzyme, RNase L [46]. The ability to identify viruses in clinical samples may prove powerful in identifying biomarkers for disease.…”
Section: Dengue Virus Typementioning
confidence: 99%